Explanation of Residents\' Experiences Concerning Medication Errors in Neonatal Intensive Care Units: A Qualitative Study - Masoumeh Seidi; Nasrin Khajeali; Soleiman Ahmady (Kerman University of Medical Sciences, 2019)
Introduction: Medication errors are a potentially hazardous accident for the patients and can be used as a measure of patient safety in the healthcare system. Neonates are the most vulnerable population because of their body size. The experiences and views of those involved in the healthcare system can be a significant source of information gathering and planning in preventing medication errors. This study aimed to explain the residents' experiences concerning medication errors in the neonatal intensive care units.  Method: This qualitative study was conducted using phenomenological method in 2017. Six residents were selected from the neonatal intensive care unit of one of the educational hospitals affiliated with Hamedan University of Medical Sciences using Purposive sampling. Data were collocted through semi-structured audio recording interviews and interviews were continued until data saturation. Finally, the interviews were completely transcribed and analyzed using Colaizzi's method. Results: With comparative analysis of data, 3 categories or themes and 9 subcategories were developed. The main themes include inefficiency in professionalism, Errors in the process of drug prescription by physicians, and individual and psychological characteristics.  Conclusion: According to the results, medication errors can be reduced by more clinical supervision on less experienced physicians in patient care, the use of electronic medical records, and the effort of pharmaceutical companies to package medicines appropriately and have efficient management